The Solar and Wind Economy in Ohio: Industry Analysis and Policy Implications - Smith, Colton; Driver, David; Michaud, Gilbert (Consilience, 2018)
After historically being driven by coal and, in more recent years, natural gas, Ohio’s energy industry has experienced notable growth in installed solar and wind capacity. Due to changes in consumer tastes and preferences, an overall decline in expenses, and environmental concerns about coal mining and hydraulic fracturing, among others, both public and industry support for renewables has grown. However, Ohio’s renewable energy policies have not consistently aligned with this support. This paper synthesizes reports and analyzes energy industry employment and capacity data in order to summarize the trends within Ohio’s present-day energy industry. After a brief surge, wind activity has stagnated, in part due to expansion of the turbine property line setbacks law. Wind employment has also been relatively erratic, seeing spikes and rapid declines that average to a growth of 13.6% per year from 2013–2016. Conversely, solar energy capacity has grown a bit more steadily due to fewer regulatory restrictions as well as supportive state net metering policies. Correspondingly, solar employment has grown more consistently at a rate of 11.3% per year during our study years. This paper highlights these trends, discusses policy implications moving forward, and makes recommendations for Ohio to stimulate the deployment of additional renewable energy capacity in future years. To accomplish this task, and to enhance sustainable development via renewable energy, we suggest that Ohio ease its wind setbacks and continues to protect the state’s renewable portfolio standard and net metering laws.